Adherence, knowledge, and difficulties related to pharmacological treatment for people with schizophrenia - Adriana Inocenti Miasso; Cristina Saemi Miamoto; Bruna Paiva do Carmo Mercedes; Kelly Graziani Giacchero Vedana (Universidade Federal de Goias, 2015)
This study aimed to verify the adherence and knowledge of people with schizophrenia as regards their prescribed pharmacotherapy, and to identify the difficulties related to the monitoring of drug therapy. It was a retrospective, cross-sectional, and descriptive study conducted in an outpatient psychiatry clinic, with 21 patients with schizophrenia, through chart review and a semi-structured interview. The data were analyzed using descriptive statistics and content analysis showing that, although 76.2% of patients adhere to treatment, most were unaware of the treatment regimen. Limitations in the administration of drugs, troublesome due to side effects and conflicts regarding the need for the drugs, were the difficulties pointed out by the study participants. The contradiction between high adherence and lack of knowledge about prescriptions reveal that promoting treatment adherence and patient safety requires interventions that address the skills and knowledge of the individual, as well as the support available for the administration of prescription drugs.